Prevalence Of Urinary Tract Infections In Diabetic Patients, Case-Control Study - Al-majedy , Kadhim (University of Thi-Qar Journal of Science, 2015)
There is evidence that patients with diabetes have an increased risk of asymptomatic bacteriuria and urinary tract infections (UTIs). UTI is the most common bacterial infection in diabetic patient.The aim of this study was to assess the prevalence of UTIs among diabetic patients and to identify the frequent of asymptomatic bacteriuria among diabetic subjects in compared with non-diabetic subject. The study population include 300 subjects .one-hundred and fifty patients with diabetes (84 female and 66 male) as a test group and 150 patients with non- diabetes mellitus (80 female and 70 male) as a control group. Between July 2012 – October2013.300 diabetic and non diabetic urine samples were collected All urine samples were processed in the lab. following standard laboratory protocol we collected patients’ personal history data..The prevalence of UTI was 50.7% in diabetic patients and 10% in non-diabetic subjects .there was significant difference in the effect of gender in both diabetic (62% female and 36%male had UTI) and non-diabetic (14% female and 7%male had UTI).there was significant increase asymptomatic bacteriuria in women within diabetic group (80% female and 62%male were asymptomatic)The frequency of UTI increase with diabetic by fourfold in comparison to that of non-diabetic subjects. the women had increased frequency of UTI more in diabetic patients than women in non-diabetic and most of them asymptomatic . The statistical significance of an association between two variables was assessed by Chi-square (X 2 ) test of independence.